Neurofilaments in health and Charcot-Marie-Tooth disease - Kotaich, Farah; Caillol, Damien; Bomont, Pascale (Frontiers in Cell and Developmental Biology, 2023)
Neurofilaments (NFs) are the most abundant component of mature neurons, that interconnect with actin and microtubules to form the cytoskeleton. Specifically expressed in the nervous system, NFs present the particularity within the Intermediate Filament family of being formed by four subunits, the neurofilament light (NF-L), medium (NF-M), heavy (NF-H) proteins and α-internexin or peripherin. Here, we review the current knowledge on NF proteins and neurofilaments, from their domain structures and their model of assembly to the dynamics of their transport and degradation along the axon. The formation of the filament and its behaviour are regulated by various determinants, including post-transcriptional (miRNA and RBP proteins) and post-translational (phosphorylation and ubiquitination) modifiers. Altogether, the complex set of modifications enable the neuron to establish a stable but elastic NF array constituting the structural scaffold of the axon, while permitting the local expression of NF proteins and providing the dynamics necessary to fulfil local demands and respond to stimuli and injury. Thus, in addition to their roles in mechano-resistance, radial axonal outgrowth and nerve conduction, NFs control microtubule dynamics, organelle distribution and neurotransmission at the synapse. We discuss how the studies of neurodegenerative diseases with NF aggregation shed light on the biology of NFs. In particular, the NEFL and NEFH genes are mutated in Charcot-Marie-Tooth (CMT) disease, the most common inherited neurological disorder of the peripheral nervous system. The clinical features of the CMT forms (axonal CMT2E, CMT2CC; demyelinating CMT1F; intermediate I-CMT) with symptoms affecting the central nervous system (CNS) will allow us to further investigate the physiological roles of NFs in the brain. Thus, NF-CMT mouse models exhibit various degrees of sensory-motor deficits associated with CNS symptoms. Cellular systems brought findings regarding the dominant effect of NF-L mutants on NF aggregation and transport, although these have been recently challenged. Neurofilament detection without NF-L in recessive CMT is puzzling, calling for a re-examination of the current model in which NF-L is indispensable for NF assembly. Overall, we discuss how the fundamental and translational fields are feeding each-other to increase but also challenge our knowledge of NF biology, and to develop therapeutic avenues for CMT and neurodegenerative diseases with NF aggregation.